Effective Genome Editing in Leishmania (Viannia) braziliensis Stably Expressing Cas9 and T7 RNA Polymerase - Espada, Caroline R.; Quilles, José Carlos; Albuquerque-Wendt, Andreia; Cruz, Mario C.; Beneke, Tom; Lorenzon, Lucas B.; Gluenz, Eva; Cruz, Angela K.; Uliana, Silvia R. B. (Frontiers in Cellular and Infection Microbiology, 2021)
Until 2015, loss-of-function studies to elucidate protein function in Leishmania relied on gene disruption through homologous recombination. Then, the CRISPR/Cas9 revolution reached these protozoan parasites allowing efficient genome editing with one round of transfection. In addition, the development of LeishGEdit, a PCR-based toolkit for generating knockouts and tagged lines using CRISPR/Cas9, allowed a more straightforward and effective genome editing. In this system, the plasmid pTB007 is delivered to Leishmania for episomal expression or integration in the β-tubulin locus and for the stable expression of T7 RNA polymerase and Cas9. In South America, and especially in Brazil, Leishmania (Viannia) braziliensis is the most frequent etiological agent of tegumentary leishmaniasis. The L. braziliensis β-tubulin locus presents significant sequence divergence in comparison with Leishmania major, which precludes the efficient integration of pTB007 and the stable expression of Cas9. To overcome this limitation, the L. major β-tubulin sequences, present in the pTB007, were replaced by a Leishmania (Viannia) β-tubulin conserved sequence generating the pTB007_Viannia plasmid. This modification allowed the successful integration of the pTB007_Viannia cassette in the L. braziliensis M2903 genome, and in silico predictions suggest that this can also be achieved in other Viannia species. The activity of Cas9 was evaluated by knocking out the flagellar protein PF16, which caused a phenotype of immobility in these transfectants. Endogenous PF16 was also successfully tagged with mNeonGreen, and an in-locus complementation strategy was employed to return a C-terminally tagged copy of the PF16 gene to the original locus, which resulted in the recovery of swimming capacity. The modified plasmid pTB007_Viannia allowed the integration and stable expression of both T7 RNA polymerase and Cas9 in L. braziliensis and provided an important tool for the study of the biology of this parasite.